A field study examination on the use and application of modern management accounting techniques adopted by manufacturing firms in Gebeng and neighbouring industrial areas / Norlaila Abdullah and Daud Mohamad - Abdullah, Norlaila; Mohamad, Daud (2004)
This study envisages to examining and investigating local management accounting practices adopted by large manufacturing firms in the quest to becoming competitive in today's business environment. Managers and top management alike rely on management accounting information in undertaking various multifaceted managerial and strategic functions. Managers often find that the larger the organizations become, the more sophisticated information they need and the more illusive it becomes. The aid of management accounting techniques and best practices enables them to draw some in depth insights needed to undertake strategies that will result to above average return required to sustain competitive edge. However, the question is: Do these companies employ management accountants to do the job? This paper further dwells on the intensity of both multinationals and high flyers domestic companies' contributions to modem management accounting evolution in addition to exploring the historical development of management accounting in the area.